Study of the formation of Kelvin-Helmholtz instability and shocks in coronal mass ejections - Murcia, Miguel Andres Paez (2018)
The coronal mass ejections (CMEs) are phenomena that evidence the complex solar activity. During the CME evolution in the solar wind (SW) the shock and sheath (Sh) are established. With these, the transfer of energy and shock thermalization have origin through several processes like instabilities and particle acceleration. Here, we present two studies related to CMEs. In the first study, we analyze the existence of the KelvinHelmholtz instability (KHI) at the interfaces CMESh and ShSW. For this purpose, we assumed two CMEs that propagate independently in the slow and fast SW. We model velocities, densities and magnetic field strengths of sheaths, and SW in the CMEs flanks, in order to solve the Chandrasekhar condition for the magnetic KHI existence. Our results reveal that KHI formation is more probably in the CME that propagate in the slow SW than in CME propagating in the fast SW. It is due to large shear flow between the CME and the slow SW. Besides we find that the interface ShSW is more susceptible to the instability. In the second study, we examine the distributions of particle acceleration and turbulence regions around CME-driven shocks with wave-like features. We consider these corrugated shock as the result of disturbances from the bimodal SW, CME deflection, irregular CME expansion, and the ubiquitous fluctuations in the solar corona. We model smooth CME-driven shocks using polar Gaussian profiles. With the addition of wave-like functions, we obtain the corrugated shocks. For both shock types are calculated the shock normal angles between the shock normal and the radial upstream coronal magnetic field in order to classify the quasi-parallel and quasi-perpendicular regions linked to the particle acceleration and turbulence regions, respectively. Our calculations show the predisposition of the shock to the particle acceleration and indicate that the irregular CME expansion is the relevant factor in the particle acceleration process. We consider that these wave-like features in shocks may be essential in the study of current problems as injection particle, instabilities, downstream-jets, and shock thermalization.